Senior Adults towards a Social Construction of Aging and Autonomy - Flores Ramirez, Maria del Carmen Carmen (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2019)
When considering the process of ageing in Latin American population it is important that senior citizens are not considered as “different” due to a culturally dominant stereotype (Courtis, 2004). Quality of life should be measured taking into consideration elements of the physical, psychological and religious conditions of a person, as well as characteristics of their environment, economy, housing and surroundings (OMS, 1995; Osorio et al., 2008, Flores and others 2011). The present study suggests the need for the application of public and social policies to support seniors through family life, healthy relationships and proper integration to their environment.